The mechanism of enriched environment repairing the learning and memory impairment in offspring of prenatal stress by regulating the expression of activity-regulated cytoskeletal-associated and insulin-like growth factor-2 in hippocampus - Guan, Su-zhen; Fu, You-juan; Zhao, Feng; Liu, Hong-ya; Chen, Xiao-hui; Qi, Fa-qiu; Liu, Zhi-hong; Ng, Tzi Bun (Environmental health and preventive medicine, 2021)
Prenatal stress can cause neurobiological and behavioral defects in offspring; environmental factors play a crucial role in regulating the development of brain and behavioral; this study was designed to test and verify whether an enriched environment can repair learning and memory impairment in offspring rats induced by prenatal stress and to explore its mechanism involving the expression of insulin-like growth factor-2 (IGF-2) and activity-regulated cytoskeletal-associated protein (Arc) in the hippocampus of the offspring. Rats were selected to establish a chronic unpredictable mild stress (CUMS) model during pregnancy. Offspring were weaned on 21st day and housed under either standard or an enriched environment. The learning and memory ability were tested using Morris water maze and Y-maze. The expression of IGF-2 and Arc mRNA and protein were respectively measured by using RT-PCR and Western blotting. There was an elevation in the plasma corticosterone level of rat model of maternal chronic stress during pregnancy. Maternal stress's offspring exposed to an enriched environment could decrease their plasma corticosterone level and improve their weight. The offspring of maternal stress during pregnancy exhibited abnormalities in Morris water maze and Y-maze, which were improved in an enriched environment. The expression of IGF-2, Arc mRNA, and protein in offspring of maternal stress during pregnancy was boosted and some relationships existed between these parameters after being exposed enriched environment. The learning and memory impairment in offspring of prenatal stress can be rectified by the enriched environment, the mechanism of which is related to the decreasing plasma corticosterone and increasing hippocampal IGF-2 and Arc of offspring rats following maternal chronic stress during pregnancy.